Formação inicial em Educação Física : o caso da disciplina de Educação Física adaptada - Gelamo, Katia Garcia (2016)
The present study had as objective to identify and how are organized the acquirement/knowledge of Physical Education for people with disabilities by the teachers that teach the discipline of Adapted Physical Education in the Physical Education Degree courses in the state of Mato Grosso. For the development of the research, we are guided in theoretical references that address the following themes: Physical Education in Brazil and Initial Formation; Teacher training in Physical Education for the inclusion of PcD; Inclusion; Disability and Adapted Physical Education. The research was characterized as descriptive, of the Survey type, with a qualitative approach. The research universe was the undergraduate courses in Physical Education in the state of Mato Grosso and the subjects were 12 (twelve) teachers working with the EFA discipline in 12 (twelve) Higher Education Institutions in the state, in addition to 84 (eighty four) academics who have already studied the discipline of these same institutions. As data collection instruments, we used the teaching plans provided by the researched institutions, a semi-structured interview for the teachers and a questionnaire for the academics. The study made it possible to understand that both teachers and academics understand the issues that permeate inclusion, the disabled and Adapted Physical Education, however, with a critical view of the educational system, point out some restrictions on the inclusion of PcD in regular education. Even with the advances that have occurred in Physical Education courses in relation to the acquirement /knowledge of Adapted Physical Education, there is still a necessity for restructuring in some aspects, both curricular and methodological, that contribute to an inclusive formation of future teachers.